A TECNOLOGIA NOS JORNAIS BRASILEIROS: CONFIGURAÇÕES TEMÁTICAS E HIPERMIDIÁTICAS DAS SEÇÕES DE TECNOLOGIA DO ESTADÃO, FOLHA DE S. PAULO, CORREIO BRAZILIENSE E GAZETA DO POVO - Dancosky, Andressa Kikuti (2015)
This master’s degree research studies the journalism about technology in Brazil. Identifies and discusses which themes are present in the technology sections from these four newspaper’s websites: Folha de S. Paulo, O Estado de S. Paulo, Gazeta do Povo and Correio Braziliense, and how they use hypermedia resources in the online content production. This study is oriented, then, from two conceptual axes: thematization and web journalism. The methodology used is a case study, reasoned from the author Robert Yin, and using as tools the collection of quantitative data, interviews with professionals responsible for the production of news content, and access to documentary sources. From this academic contribution, it is expected to collaborate on strengthening journalism as a field of knowledge and professional practice, and the technology as a socially relevant theme.